Procedures for appointing the members of constitutional courts - a comparative study with reference to the law of the Federal Supreme Court in Iraq - Assistant Professor Dr. Mohamed Hamid Abd,; Assistant Professor Dr.Hussein Jabr Hussein Shuwaili, (The college of law and political science journal, 2023)
.